2022
DOI: 10.3390/ijms23168955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Shock Preconditioning on Pressure Injury Prevention via Hsp27 Upregulation in Rat Models

Abstract: Pressure injury (PI) prevention is a huge industry and involves various interventions. Temperature and moisture are important factors for wound healing; however, the active mechanism by which “moist heat” affects PI prevention has not yet been clarified. Thus, we explored the protective and therapeutic effects of hydrotherapy on PI based on the preconditioning (PC) principle, which might be useful for clinical practice. This study aimed to investigate the preventive mechanisms of heat shock preconditioning on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Various combinations of effects are known, for example, when a chemical effect is manifested by a physical one or vice versa. The preconditioning effect is known at the level of the organism [88,89], physiology [90,91], tissues [8,92], cells [93], and biological residues, liquids, aqueous colloids, and solutions [94,95], and, as shown in this study, in water.…”
Section: Influence Of Magnetic Field and Mechanical Action By Pipetti...mentioning
confidence: 88%
“…Various combinations of effects are known, for example, when a chemical effect is manifested by a physical one or vice versa. The preconditioning effect is known at the level of the organism [88,89], physiology [90,91], tissues [8,92], cells [93], and biological residues, liquids, aqueous colloids, and solutions [94,95], and, as shown in this study, in water.…”
Section: Influence Of Magnetic Field and Mechanical Action By Pipetti...mentioning
confidence: 88%
“…It is thought that this situation is similar to the hormesis phenomenon. Microinjury of the ear skin with the effect of microneedling may have reduced the inflammatory effect of edema formation with xylene due to the preconditioning [73,74].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…It has been demonstrated that overexpression of HSPB1 can inhibit erastin‐induced ferroptosis in cancer cells and that this process was dependent on HSF1, 104 underscoring the key role of HF1‐HSPB1 in inhibiting ferroptosis. Xu et al showed that heat shock preconditioning had a preventive effect on pressure injuries via HSP27 upregulation in rat models 105 . Although it is currently unclear whether heat shock proteins can mitigate ferroptotic cell death in the context of DTIs, considering the pathogenic role of ferroptosis in DTIs and the protective role of HSPB1 in pressure injuries, this may provide new insights into the potential role of ferroptosis in the pathophysiological processes of DTIs.…”
Section: Implications Of Ferroptosis In Dtismentioning
confidence: 99%